Menggali Potensi Usaha Kuliner Sebagai Peluang Peningkatan Keuangan Keluarga - Suswati Nasution; Suwarni Suwarni; Ida Anggriani; Ermy Wijaya; Dennis Rydarto Tambunan (Jurnal Dehasen Untuk Negeri, 2023)
The attractiveness of the culinary business lies in food and beverage products that have uniqueness, value and high selling power, with a variety of foods, man-made products which are objects that attract consumers to buy. And to make it now is not a difficult thing, there are many culinary recipes and examples that can be innovated and created into new things that attract people's interest to buy them. The community of Rt.31.Rw.07 which is on Jalan Merawan Sawah Lebar Bengkulu, is located very close to the Dehasen University Bengkulu campus, also close to several elementary and advanced schools. This can be used as motivation to open a business, because the location is busy and it would be great if you could work with the campus or school as a supplier of consumption in the form of snacks if there were school or campus activities. For this reason, we, the Campus Service Team, consist of five (5) service groups that for a full month held community service for the residents of RT.31 Rw.07, Jalan Merawan, Sawah Lebar Village, Ratu Agung District, Bengkulu City. Where one form of service provided is learning about entrepreneurship regarding exploring the potential of culinary businesses that already exist or are just about to start a business, with the aim of increasing knowledge and useful activities that lead to an increase in family finances. Keywords: Potential, business, Culinary